Observations and analyses of the first two hydraulic stimulations in the Pohang geothermal development site, South Korea. (November 2020) - Park, Sehyeok; Kim, Kwang-Il; Xie, Linmao; Yoo, Hwajung; Min, Ki-Bok; Kim, Myungsun; Yoon, Byoungjoon; Kim, Kwang Yeom; Zimmermann, Günter; Guinot, Frédéric; Meier, Peter
Highlights: First two hydraulic stimulations at Pohang enhanced geothermal sites were presented. Tensile fracture extension and hydraulic jacking occurred in PX-2 at high pressures. Hydraulic shearing and jacking occurred in PX-1 at much lower pressures than PX-2. Induced seismicity was more active during shut-in and proportional to injected volume. Lost circulation in PX-2 possibly caused differences between the two wells. Abstract: We present key observations and analyses of the first and second stimulations conducted at the Pohang enhanced geothermal system (EGS) site in Korea in 2016. The first hydraulic stimulation was conducted in the PX-2 well of 4.3 km depth, with the maximum wellhead pressure of 89.2 MPa, the maximum injection rate of 46.8 L/s, and a total injected volume of 1970 m 3 . The first stimulation showed non-linear and reversible fracture-opening behavior with injection pressure increase. The stimulation mechanism of PX-2 is interpreted as a combination of tensile fracture extension and hydraulic jacking. The second hydraulic stimulation was conducted in the PX-1 well of 4.2 km depth, with the maximum wellhead pressure of 27.7 MPa, the maximum injection rate of 18.0 L/s, and a total injected volume of 3907 m 3 . The fracture-opening pressure of PX-1 was evaluated from the clear pressure peaks and the pressure at differential injectivity increase, and was drastically lower than that of PX-2. The transmissivity of PX-1 permanently increased by 6.4 times during the second stimulation. The wellhead injectivity of PX-1 was 3.6 times as high as that of PX-2 at the same injection rate. The stimulation mechanism in PX-1 is interpreted as a combination of hydraulic shearing and hydraulic jacking of unmated or shear-dilated fracture. Both stimulations in the two wells showed consistently greater seismicity rate and magnitude during the shut-in phases than during the preceding injection phases. A close correlation between the injected fluid volume and seismic magnitude was observed in both wells, and the seismic events induced by the two stimulations were in general below the maximum magnitude envelopes expected by the previous studies. Despite the close distance of approximately 600 m in the same rock formation, the two wells showed distinctly different behavior in terms of the overall pressure ranges, pressure peaks, pressure for injectivity increases, transmissivity changes, and the stimulation mechanisms due possibly to the heavy mud and lost circulation material used during the drilling and completion of PX-2. The contrasting hydromechanical responses observed in the same reservoir at the two nearby wells emphasize the importance of proper drilling and completion with close consideration of stimulation strategy.